2014
DOI: 10.15274/inr-2014-10047
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Intracranial Aneurysms in the Flow Diverter Era: Frequency of Use and Results in a Consecutive Series of 550 Treatments in a Single Centre

Abstract: Flow diverter devices became available in our department in 2009. We considered treatment with flow diverters only in patients with aneurysms not suitable for surgery or conventional endovascular techniques. This paper presents our preliminary experience with flow diverters in a consecutive series of 550 endovascular aneurysm treatments. Between January 2009 and July 2013, 550 endovascular treatments for intracranial aneurysms were performed. Of these, 490 were first-time aneurysm tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Far distal aneurysms (14.2% to 38.2%; p < 0.0001) and the presence of an intracranial hematoma (8.9% to 20.1%; p = 0.0015) were the actual top reasons for microsurgical clipping in our study. Besides the standard coiling procedure many new endovascular occlusion techniques and devices like stent-assisted coiling procedures, WEB-devices and flow-diverters have been developed, which allow the treatment of aneurysms with unfavourable neck configuration [ 11 17 ]. Moreover, the ISAT-study resulted in a preference of the endovascular procedure for occlusion of ruptured intracranial aneurysms if both procedures (clipping and coiling) were possible [ 4 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Far distal aneurysms (14.2% to 38.2%; p < 0.0001) and the presence of an intracranial hematoma (8.9% to 20.1%; p = 0.0015) were the actual top reasons for microsurgical clipping in our study. Besides the standard coiling procedure many new endovascular occlusion techniques and devices like stent-assisted coiling procedures, WEB-devices and flow-diverters have been developed, which allow the treatment of aneurysms with unfavourable neck configuration [ 11 17 ]. Moreover, the ISAT-study resulted in a preference of the endovascular procedure for occlusion of ruptured intracranial aneurysms if both procedures (clipping and coiling) were possible [ 4 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the serious complications associated with PED embolization are the parent artery occlusion due to the in-stent thrombosis. Although there are some reports of periprocedural in-stent thrombosis, 2 4) those of delayed in-stent thrombosis are scarce. Chiu et al (2015) reported two patients with delayed PED occlusions.…”
Section: Discussionmentioning
confidence: 99%
“…ticulostriate arteries (LSAs) or other arterial trunks, which can cause unintended occlusions and ischemic complications, 10,16,40,41,46,47 and devices such as intraaneurysmal flow diverters or bifurcation stents are new and unproven and have not been compared rigorously with the microsurgical standard. 5,27 Complex MCA aneurysms can be managed with bypass procedures when conventional clipping fails and a parent artery requires deliberate occlusion.…”
mentioning
confidence: 99%